Fabrication and performance evaluation of vertical farming structure for homesteads - AMEENA R. K; Anjitha Krishna P. R; Sreekutty Suresh V; Er. Priya G. Nair (Guide) (Tavanur 2015 Department of Land & Water Resources and Conservation Engineeringy)
aimed to fabricate a vertical farming structure suited to flat balcony in KCAET and to compare the performance evaluation of crops under vertical farming structure and potted cultivation.
Fabrication and performance evaluation of vertical farming structure for homesteads